2016
DOI: 10.1155/2016/1951707
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bone Metabolism in Critically Ill Patients Using CTx and PINP

Abstract: Background. Prolonged immobilization, nutritional and vitamin D deficiency, and specific drug administration may lead to significant bone resorption. Methods and Patients. We prospectively evaluated critically ill patients admitted to the ICU for at least 10 days. Demographics, APACHE II, SOFA scores, length of stay (LOS), and drug administration were recorded. Blood collections were performed at baseline and on a weekly basis for five consecutive weeks. Serum levels of PINP, β-CTx, iPTH, and 25(OH)vitamin D w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
(42 reference statements)
0
6
0
1
Order By: Relevance
“…A previous prospective observational study conducted on 28 adult patients with prolonged critical illness also described BTM levels at 5 weeks, reporting high beta-CTx levels in 45% of subjects at admission, increasing to more than 80% of subjects week 1 and 2, and more than 50% of subjects at week 5. In contrast, P1NP (bone formation marker) concentrations were reduced in 55% of subjects at admission to ICU and 10% of subjects by week 5 [37].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A previous prospective observational study conducted on 28 adult patients with prolonged critical illness also described BTM levels at 5 weeks, reporting high beta-CTx levels in 45% of subjects at admission, increasing to more than 80% of subjects week 1 and 2, and more than 50% of subjects at week 5. In contrast, P1NP (bone formation marker) concentrations were reduced in 55% of subjects at admission to ICU and 10% of subjects by week 5 [37].…”
Section: Discussionmentioning
confidence: 90%
“…Thirteen studies (case series or cohort studies) have been published that include short-term evaluations of BTMs as outcome in ICU patients [9,25,[27][28][29][30][31][32][33][34][35][36][37]. All studies that evaluated BTMs described an initial increase of markers of bone reabsorption, suggesting an increased osteoclastic activity in ICU patients [1,9,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. One study also measured osteoclast precursors and mature osteoclasts in serum and described a significant increase in osteoclast precursors in ICU patients compared to controls [40].…”
Section: Discussionmentioning
confidence: 99%
“…No studies on predictive value of bone turnover status for hospital outcomes in orthogeriatric patients have been reported. Previous studies found in critically ill patients on admission significantly elevated bone resorption markers, including bCTX levels ( 129 - 133 ), and low-normal P1NP levels 132 , 133 . Lower BMD was shown to predict myocardial infarction in men and women during 5.7 years of follow-up 97 .…”
Section: Discussionmentioning
confidence: 90%
“…Uncoupling of osteoclast and osteoblast regulation is known to occur in critical illness. Bone resorption starts immediately; CTX-1 values peak two weeks after baseline and return to initial values by four weeks [17].…”
Section: Discussionmentioning
confidence: 99%